Temperature has considerable effects on plasma and muscle antibiotic concentrations in Atlantic salmon (Salmo salar) - Zanuzzo, Fábio S. [UNESP]; Peroni, Ellen de Fátima C.; Sandrelli, Rebeccah M.; St-Hilaire, Sophie; O'Brien, Nicole; Gamperl, Anthony K. (Elsevier, 2022)
Climate change is increasing ocean temperatures, and this has created several concerns / challenges for the Atlantic salmon aquaculture industry. For example, high temperatures may lower tissue antibiotic concentrations and decrease their effectiveness at treating a variety of bacterial diseases. To the best of our knowledge, no controlled studies using industry-relevant treatment protocols have measured tissue/plasma levels of the most used antibiotics under conditions that mimic summer temperatures experienced by sea-caged salmon in Atlantic Canada. Thus, we held salmon at 12 °C (control group), or incrementally increased temperature to 16 and 20 °C (at 1 °C every 4 days), and then fed them with therapeutic doses of tetracycline (100 mg kg body weight−1 day−1) and florfenicol (10 mg kg body weight−1 day−1) for 15 and 10 days, respectively. Thereafter, we measured plasma and muscle antibiotic concentrations during the withdrawal phase (i.e., at 18 h, and 3 and 10 days for tetracycline; and 18, 24 and 72 h for florfenicol) using high-performance liquid chromatography. Muscle and plasma tetracycline concentrations at 18 h post-feeding were highest in fish at 12 °C (i.e., 254 ± 45 and 2577 ± 298 ppb, respectively; mean ± SEM) compared to fish at 16 °C (7.5 and 30% lower, respectively) and 20 °C (62 and 41% lower, respectively). These levels, and the difference amongst the groups (i.e., temperatures), decreased significantly over the withdrawal period. For example, plasma concentrations were below the limit of quantification (LOQ; i.e., < 66 ppb) for tetracycline in all groups by 10 days post-treatment, whereas muscle concentrations were ~ 700 ppb. Plasma and muscle florfenicol concentrations were also greatest at 18 h post-treatment in fish held at 12 °C (254 ± 45 and 2221 ± 387 ppb, respectively) as compared to fish held at 16 °C (70 and 67% lower, respectively). In contrast, only one fish held at 20 °C had values above this antibiotic's LOQ (250 ppb) at this sampling point. Interestingly, the levels of florfenicol amine in the muscle and plasma were not affected by temperature and similar amongst groups. Collectively, our results show that high temperatures lower tissue antibiotic concentrations in Atlantic salmon and suggest that water temperature should be considered when conducting antibiotic treatments to avoid under-dosing; especially in the case of florfenicol.
Keywords: Aquaculture; Climate change; Florfenicol; Global warming; Tetracycline